An Improved Double Fuzzy PI Controller For Shunt Active Power Filter DC Bus Regulation - Nabil Elhaj; Moulay Brahim Sedra; Tarik Jarou; Hind Djeghloud (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper targets to demonstrate the importance of the choice of the algorithm references detection to be applied with a double fuzzy PI corrector (DFPI) for the control and the regulation of a shunt active power filter (SAPF) DC bus voltage. In a previous work, the synchronous reference frame (SRF) algorithm was applied and gave satisfactory results. In the present paper, the SRF is substituted by the positive sequence of the fundamental of the source voltage algorithm (PSF) which offered better results regarding the power quality of the considered main utility feeding a variable DC RL load throughout a diode bridge. The results were carried out using computer simulation perfomed under MATLAB/Simulink environment. To make the obtained results more convenient, a comparison between the couples (SRF, PI), (PSF, PI), (SRF, DFPI), (PSF, DFPI) is added to prove the effectiveness of the couple (PSF, DFPI) in satisfying the compromise between a good regulation of the SAPF DC bus voltage and a good quality of filtering resulting in an improved quality of power.